A Two Channel Analog Front end Design AFE Design with Continuous Time Σ-Δ Modulator for ECG Signal - Mohammed Abdul Raheem; K Manjunathachari (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this context, the AFE with 2-channels is described, which has high impedance for low power application of bio-medical electrical activity. The challenge in obtaining accurate recordings of biomedical signals such as EEG/ECG to study the human body in research work. This paper is to propose Multi-Vt in AFE circuit design cascaded with CT modulator. The new architecture is anticipated with two dissimilar input signals filtered from 2-channel to one modulator. In this methodology, the amplifier is low powered multi-VT Analog Front-End which consumes less power by applying dual threshold voltage. Type -I category 2 channel signals of the first mode: 50 and 150 Hz amplified from AFE are given to 2nd CT sigma-delta ADC. Depict the SNR and SNDR as 63dB and 60dB respectively, consuming the power of 11mW. The design was simulated in a 0.18 um standard UMC CMOS process at 1.8V supply. The AFE measured frequency response from 50 Hz to 360 Hz, depict the SNR and SNDR as 63dB and 60dB respectively, consuming the power of 11mW. The design was simulated in 0.18 m standard UMC CMOS process at 1.8V supply. The AFE measured frequency response from 50 Hz to 360 Hz, programmable gains from 52.6 dB to 72 dB, input referred noise of 3.5 μV in the amplifier bandwidth, NEF of 3.